Pengaruh Remunerasi, Motivasi dan Kepuasan Kerja Terhadap Kinerja Pegawai Universitas Islam Negeri Sumatera Utara Medan - Hijja Mardhiya Nasution; Sri Sudiarti; Isnaini Harahap (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2019)
This study aims to analyze the effect of remuneration, motivation and job satisfaction on employee performance at UIN North Sumatra Medan both partially and simultaneously. The research design used is quantitative research using multiple linear regression analysis techniques supported by classic assumption tests and statistical tests with the help of SPSS 22 program. Data collection techniques in this study by distributing questionnaires to the sample in this study were 153 employees of education staff UIN North Sumatra Medan. From the results of t-statistic research that the variable remuneration significantly influences employee performance. The t-statistic test results of motivation variables significantly influence employee performance. T-statistic test results that variable job satisfaction significantly affect employee performance. Simultaneously it is obtained that F-count is greater than F-table and can also be seen in the probability value smaller than the level of significance. It can be concluded that the variable remuneration, motivation, and job satisfaction jointly influence the performance of UIN North Sumatra Medan employees